The Literature of Employee Representation - Gemmill, Paul F. (Quarterly Journal of Economics, 1928)
Journal Article The Literature of Employee Representation Get access Paul F. Gemmill Paul F. Gemmill University of Pennsylvania Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 42, Issue 3, May 1928, Pages 479–494, https://doi.org/10.2307/1884788 Published: 01 May 1928